Enhancing Early Childhood Art Ability Through Natural Material Collage Activities at TK Islam Raudhatul Jannah - Shally Erlika Elga (Journal of Teaching and Education, 2025)
This classroom action research (CAR) aims to describe the improvement of early childhood art skills, especially collage skills, through the use of natural materials at Raudhatul Jannah Islamic Kindergarten. The background of the problem shows low art skills as reflected in the average precycle score of 50.00% with a suboptimal level of development. The subjects of the study were 15 children (8 boys and 7 girls) from Group A of Raudhatul Jannah Islamic Kindergarten in the 2025/2026 academic year. This study was conducted in two cycles, where each cycle consisted of planning, action implementation, observation, and reflection. Data collection instruments were observation sheets and documentation of work results. The results of the study showed a significant increase from each cycle. In Cycle I, the percentage of completion reached 66.67%, but the target success indicator (80%) had not been achieved. After improvements were made in Cycle II, the percentage of completion increased sharply to 93.33%. This improvement demonstrates that gluing activities using natural materials (such as dried leaves, seeds, and twigs) are effective as a learning strategy for developing art and fine motor skills in early childhood. This study recommends that early childhood education teachers integrate natural materials as the primary medium in art instruction